2012
DOI: 10.1002/cpp.1790
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Comorbidity is Associated with Increased Skill Deficits

Abstract: Lower skill levels are associated with higher comorbidity and higher level of psychopathology of patients. There is evidence for specific skill profiles within different clinical subsamples. The improvement of skills that can impact recovery from mental disorders is especially relevant for patients with multiple diagnoses. It makes sense to assess the different skills independently and consider them separately when planning interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…In the first step of the analysis, we checked the bivariate correlations (Spearman's Rho) between the variables (pretreatment). The highest correlations between skills and psychopathology exist for relaxation ability ( r = −.53, p < .001) and emotion regulation ( r = −.49, p < .001); Stenzel et al () found similar correlations. In the present study, we found a significant relationship between psychopathology and disability ( r = .61, p < .001).…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…In the first step of the analysis, we checked the bivariate correlations (Spearman's Rho) between the variables (pretreatment). The highest correlations between skills and psychopathology exist for relaxation ability ( r = −.53, p < .001) and emotion regulation ( r = −.49, p < .001); Stenzel et al () found similar correlations. In the present study, we found a significant relationship between psychopathology and disability ( r = .61, p < .001).…”
Section: Resultsmentioning
confidence: 90%
“…Considering the link between skills and comorbidity and psychopathology (Hofmann et al., ; Stenzel et al., ) and between psychopathology and disability (Bijl & Ravelli, ), the subsequent analyses were controlled for general psychopathology. The results showed that, in addition to psychopathology, stress management remained as a “predictor” of disability cross‐sectionally.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mehreren Studien zufolge ergeben sich sowohl bei klinischen als auch nichtklinischen Stichproben gute psychometrische Kennwerte, und die Ergebnisse sprechen dafür, dass sich die einzelnen Fertigkeitsbereiche inhaltlich voneinander abgrenzen lassen [Stenzel et al, 2010;Stenzel und Rief, 2011]. Studien zeigen ferner substanzielle Zusammenhänge zwischen Fertigkeiten und verschiedenen Stö-rungsbildern, der allgemeinen Psychopathologie und dem Therapieerfolg [Fehlinger et al, 2013a,b;Hofmann et al, 2015;Stenzel et al, 2013]. Die Informationen über die Fertigkeiten können zu einem Funktionsprofil einer Person integriert, vor dem Hintergrund des jeweiligen Störungsbildes interpretiert und für die Ableitung psychotherapeutischer Interventionen genutzt werden.…”
Section: Diagnostik Von Fertigkeitenunclassified